The faith as fundamental condition to take the baptism - JANCZEWSKI, ZBIGNIEW (Prawo Kanoniczne, 2013)
The faith and the baptism are inseparable. In the beginning of history of the church the baptism was taking adult people. They has the faith before this sacrament. The children was baptizing together with his parents. Today in many countries candidates to baptism are children, to young, to have mature faith. They take sacrament on the faith of their father, mother, sponsors and Church. The article consists of three parts. First is about historical aspect of the problem. The next shows theological conception of the faith. The last part is about faith of adult people who takes the sacrament of baptism, and parents and sponsors of children who takes the baptism, based on canon and liturgical law.